Pemaknaan Khalayak Terhadap Maskulinitas Melalui Fashion Hijab Pada Akun Instagram @strngrrr - Devi Triya Oktaviyani; Sukma Ari Ragil Putri (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Intan Khasanah is one of the hijab fashion influencers who looks masculine. Through her Instagram account @strngrrr, she shares thoughts that not all women who wear hijab must look according to the standards or feminine stereotypes that exist in society in general and not all masculine appearances can only be owned by a man, and by wearing a hijab they can still look cool and fashionable. However, the meaning of the audience is not necessarily in line with or even accept his ideas. Thus, this research is interesting to be investigated further with the aim of describing the meaning of the audience towards masculinity in hijab fashion in the photos uploaded by Intan Khasanah. This study uses descriptive qualitative methods and Stuart Hall reception analysis, and is supported by Butler's theory of gender performativity. The results obtained from the meaning of audiences in this study are varied, but have a tendency to interpret them in a negotiated manner which means they will not immediately receive media messages and interpret them for granted, but are carried out through negotiations according to opinions about the experiences of each audience..